Facilitating anaplastic thyroid cancer specialized treatment: A model for improving access to multidisciplinary care for patients with anaplastic thyroid cancer. Issue 7 (28th April 2017) - Cabanillas, Maria E.; Williams, Michelle D.; Gunn, G. Brandon; Weitzman, Steven P.; Burke, Laura; Busaidy, Naifa L.; Ying, Anita K.; Yiin, Yeh Hung; William, William N.; Lu, Charles; Lai, Stephen Y.
Abstract: Background: Anaplastic thyroid cancer (ATC) is a highly aggressive thyroid cancer. Several treatment trials are available, but the number of eligible patients to participate is very low because of the rarity and aggressiveness of the disease. Methods: Facilitating Anaplastic Thyroid Cancer Specialized Treatment (FAST) is a quality improvement project aimed at decreasing time from referral to disposition (scheduling of first appointment) to our institution. After identifying reasons for delays, we created a new process flow specifically for patients with ATC allowing patients to be scheduled immediately. Results: Historical data revealed a mean referral to disposition time for patients with ATC of 8.7 days before our intervention. After the intervention, the mean referral to disposition time was reduced to 0.5 days. Participation in treatment trials for all patients with ATC was 34%. Conclusion: Since the implementation of FAST, the access time has decreased and the number of successful referrals for ATC has increased significantly.